METODOLOGI PENELITIAN HUKUM EMPIRIS DALAM MENGKAJI EFEKTIVITAS PENEGAKAN HUKUM - Sifirman Zalukhu; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study formulates a methodological framework for empirical legal research assessing law enforcement effectiveness. A structured literature review was conducted using a PICO framework adapted to socio-legal inquiry. Population refers to law-enforcement studies and settings; intervention concerns the application of legal norms and official action; comparison covers before-and-after conditions, jurisdictions, institutions, or law in books versus law in action; and outcomes include compliance, access, consistency, procedural justice, case resolution, and perceived legitimacy. Sources comprise journal articles published in 2020–2026, methodology books, and legislation. The thematic synthesis indicates that effectiveness cannot be adequately inferred merely from the existence of rules or the volume of coercive action. Measurement must integrate legal substance, institutional capacity and integrity, facilities, community responses, legal culture, and consequences for target groups. The proposed design combines indicator operationalisation, triangulation of documents, interviews, observation and administrative records, defensible sampling, data-quality checks, and an explicit explanation of the relationship between norms, processes, and outcomes. This framework improves the validity of assessment and supports contextual and testable recommendations for law enforcement reform..